Non-invasive, real-time reporting drug release in vitro and in vivo. Issue 32 (23rd March 2015) - Zhang, Yanfeng; Yin, Qian; Yen, Jonathan; Li, Joanne; Ying, Hanze; Wang, Hua; Hua, Yuyan; Chaney, Eric J.; Boppart, Stephen A.; Cheng, Jianjun
Abstract : An in vitro and in vivo drug-reporting system is developed for real-time monitoring of drug release via the analysis of the concurrently released near-infrared fluorescence dye. Abstract : We developed a real-time drug-reporting conjugate (CPT-SS-CyN) composed of a near-infrared (NIR) fluorescent cyanine-amine dye (CyN), a disulfide linker, and a model therapeutic drug (camptothecin, CPT). Treatment with dithiothreitol (DTT) induces cleavage of the disulfide bond, followed by two simultaneous intramolecular cyclization reactions with identical kinetics, one to cleave the urethane linkage to release the NIR dye and the other to cleave the carbonate linkage to release CPT. The released CyN has an emission wavelength (760 nm) that is significantly different from CPT-SS-CyN (820 nm), enabling easy detection and monitoring of drug release. A linear relationship between the NIR fluorescence intensity at 760 nm and the amount of CPT released was observed, substantiating the use of this drug-reporting conjugate to enable precise, real-time, and non-invasive quantitative monitoring of drug release in live cells and semi-quantitative monitoring in live animals.